Governing Jihad: Islamic Militias, State Security Forces, and Religious Policing in Post-Conflict Poso, Indonesia - Muhammad Najib Azca; Moh. Zaki Arrobi (Al-Jami'ah: Journal of Islamic Studies, 2026)
This article examines the complex entanglements between state security forces and Islamic non-state actors in the dynamics of security and insecurity in post-conflict Poso, Indonesia. Drawing on and expanding the notion of “security blurs” proposed by Diphoorn and Grassiani, we investigate how Islamic religious discourses, authorities, and practices are inextricably woven into the fabric of security governance in this post-conflict context. The article reveals that policing against religious terrorism in Poso fundamentally involves engagements and collaborations with diverse Islamic non-state security actors, ranging from former jihadist combatants and ex-convicted terrorists to local Islamic religious leaders and community networks. This study argues that the entanglement of Islamic religious actors with state security forces simultaneously produces both security and insecurity. This form of “religious policing”—shaped significantly by Islamic norms, discourses, and actors—challenges the prevailing assumption in modern policing scholarship that security governance must necessarily be secular and impartial.[Artikel ini mengkaji keterkaitan kompleks antara aparat keamanan negara dan aktor-aktor Islam non-negara dalam dinamika keamanan dan ketidakamanan di Poso, Indonesia, pasca-konflik. Dengan mengacu pada sekaligus mengembangkan konsep “security blurs” yang dikemukakan oleh Diphoorn dan Grassiani, kami menyelidiki bagaimana wacana, otoritas, dan praktik keagamaan Islam terjalin erat dalam struktur tata kelola keamanan dalam konteks pasca-konflik ini. Artikel ini mengungkapkan bahwa penegakan hukum terhadap terorisme bermotif agama di Poso pada dasarnya melibatkan interaksi dan kolaborasi dengan berbagai aktor keamanan non-negara Islam, mulai dari mantan kombatan jihad, mantan terpidana teroris, hingga pemimpin agama Islam lokal dan jaringan masyarakat. Studi ini berpendapat bahwa keterkaitan antara aktor-aktor agama Islam dengan pasukan keamanan negara secara bersamaan menghasilkan keamanan dan ketidakamanan. Bentuk religious policing (penegakan hukum berbasis agama) yang secara signifikan dibentuk oleh norma, wacana, dan aktor Islam ini menantang asumsi yang berlaku dalam kajian penegakan hukum modern bahwa tata kelola keamanan harus bersifat sekuler dan imparsial.]